PERTANGGUNGJAWABAN PIDANA DOKTER HEWAN TERHADAP MALPRAKTIK DI KLINIK HEWAN - Lucky Riyandi Chanuraya; Sudarto (LEX OMNIBUS : Jurnal Hukum Tata Negara dan Administrasi Negara, 2025)
This research is motivated by the absence of a specific law (lex specialis) specifically regulating the criminal liability of veterinarians in malpractice cases in Indonesia. This lack of regulation creates legal uncertainty, both for veterinarians as professional medical personnel and for animal owners who suffer losses due to medical negligence. To date, cases of alleged veterinary malpractice can only be processed under general articles in the Criminal Code, such as Articles 359 and 302 of the Indonesian Criminal Code. The purpose of this study is to analyze the applicable legal basis and evaluate the forms of criminal liability that can be imposed on veterinarians in clinical practice. This study uses a normative juridical method supported by an empirical approach through interviews. The theories used include the theory of criminal liability, the principle of lex artis, and the principle of informed consent in assessing professional negligence. Data were obtained through a literature review of laws and legal doctrines, as well as interviews with veterinarians and animal owners. The results indicate that weak implementation of professional standards and low public legal literacy often result in malpractice cases going unreported or not being legally pursued. This study concludes the importance of establishing a Veterinary Practice Law that comprehensively regulates criminal and administrative responsibilities, as well as oversight mechanisms. It is recommended that the government immediately formulate such regulations and strengthen the role of professional organizations in enforcing ethics and legal education.